Coronavirus infection and chronic lung allograft dysfunction: a retrospective cohort study - Lydia Canham; Carolin Steinack; René Hage; Maurice Roeder; Silvia Ulrich; Gernot Ortmanns; Silvan Vesenbeckh; Thomas Gaisl; Macé M. Schuurmans (Swiss Medical Weekly)
INTRODUCTION: Long-term survival in lung transplant recipients is limited by chronic lung allograft dysfunction, which can be triggered by respiratory tract infections.